2001
DOI: 10.1002/cfg.85
|View full text |Cite
|
Sign up to set email alerts
|

A genomic approach for the identification and classification of genes involved in cell wall formation and its regulation in Saccharomyces cerevisiae

Abstract: Using a hierarchical approach, 620 non-essential single-gene yeast deletants generated by EUROFAN I were systematically screened for cell-wall-related phenotypes. By analyzing for altered sensitivity to the presence of Calcofluor white or SDS in the growth medium, altered sensitivity to sonication, or abnormal morphology, 145 (23%) mutants showing at least one cell wall-related phenotype were selected. These were screened further to identify genes potentially involved in either the biosynthesis, remodeling or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
123
0
3

Year Published

2001
2001
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 148 publications
(135 citation statements)
references
References 65 publications
9
123
0
3
Order By: Relevance
“…As shown in Fig. 1, Slt2p was found to be activated in both itc1 strains, thus indicating that the previously reported activation of this MAPK (de Groot et al, 2001) is not mating type-specific. These results suggest that the aberrant morphology and the constitutive activation of the pheromone pathway, detected only in the MATa itc1 mutant cells, are not related to the cell wall phenotype.…”
Section: Resultssupporting
confidence: 68%
See 2 more Smart Citations
“…As shown in Fig. 1, Slt2p was found to be activated in both itc1 strains, thus indicating that the previously reported activation of this MAPK (de Groot et al, 2001) is not mating type-specific. These results suggest that the aberrant morphology and the constitutive activation of the pheromone pathway, detected only in the MATa itc1 mutant cells, are not related to the cell wall phenotype.…”
Section: Resultssupporting
confidence: 68%
“…itc1 mutants show mating type-independent activation of the cell integrity pathway ITC1 has been identified among a group of genes whose deletion results in defects in cell wall integrity (de Groot et al, 2001). The systematic screening of 620 MATa mutants for different cell wall-related phenotypes revealed the itc1 mutant to be sensitive to the presence of calcofluor white or caffeine in the growth medium, and to show constitutive activation of Slt2p/Mpk1p, the MAPK of the cell wall integrity signalling pathway.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results indicate that the suppressor genes work in parallel to set the normal level of caffeine resistance in wild-type cells. The fact that none of the suppressor genes was previously identified in largescale screens examining caffeine sensitivity (de Groot et al, 2001;Dudley et al, 2005) highlights the importance of multiple genetic approaches to studying a given cellular process.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the widespread human consumption of caffeine-containing beverages and foods makes understanding the molecular details of its effects on cells a medically relevant endeavour (Bode and Dong, 2007;Sabisz and Skladanowski, 2008). Although there are numerous reports of budding yeast mutations that confer caffeine sensitivity (de Groot et al, 2001;Dudley et al, 2005;SGD Project, 2009), relatively few mutations have been shown to cause caffeine resistance. Notably, certain mutations in the kinase domain and FK506 binding protein-interacting domain (FRB) of TOR confer synergistic caffeine resistance (Reinke et al, 2006), and screens for caffeine-resistant mutants in Schizosaccharomyces pombe have yielded strains with mutations in genes that function in oxidative stress response mediated by the transcription factor Pap1 (Benko et al, 1997(Benko et al, , 1998(Benko et al, , 2004Kumada et al, 1996).…”
Section: Introductionmentioning
confidence: 99%